اہلِ کتاب کے ذبیحہ پر تسمیہ کی شرط: قرآنی نصوص و فقہی آراء کا تحقیقی و تقابلی مطالعہ: The Requirement of Tasmiyah (Invocation of Allah’s Name) on the Slaughter of the People of the Book: A Critical and Comparative Study of Qur’anic Texts and Juristic Opinions (Al-Qamar, 2025)
This research investigates the juristic and exegetical debate surrounding the requirement of tasmiyah—the invocation of Allah’s name—when consuming the slaughtered meat of the Ahl al-Kitāb (People of the Book). The study critically examines relevant Qur’anic texts, Prophetic traditions, and classical juristic interpretations across the four major Sunni schools of law (Ḥanafī, Mālikī, Shāfiʿī, and Ḥanbalī), alongside select opinions from contemporary scholars. Through a textual and comparative methodology, the research explores two central questions:(1) whether the permissibility granted in Sūrat al-Māʾidah (5:5)— “The food of those who were given the Scripture is lawful for you”—is absolute or conditional upon tasmiyah, (2) how classical jurists reconciled this verse with others emphasizing the necessity of mentioning Allah’s name during slaughter (6:118–121). The paper analyzes how differing hermeneutical approaches—literalist, contextualist, and maqāṣid-oriented—produced varying legal conclusions. Some jurists view tasmiyah as a non-negotiable act of devotion tied to tawḥīd and ritual purity, while others interpret the verse of al-Māʾidah as a manifestation of divine leniency towards the People of the Book. The study also considers the implications of modern slaughterhouse practices, interfaith dietary regulations, and ethical concerns in a globalized context. Ultimately, this research demonstrates that the issue of tasmiyah is not merely a matter of dietary law, but an epistemological question concerning the balance between revelatory universality and ritual particularity within Islamic jurisprudence.
Keywords: Tasmiyah, Ahl al-Kitāb, Qur’anic hermeneutics, Islamic law, slaughter, halal, fiqh, Sūrat al-Māʾidah, comparative jurisprudence, modern ethics